2006
DOI: 10.1159/000091721
|View full text |Cite
|
Sign up to set email alerts
|

Treating Auditory Hallucinations by Transcranial Magnetic Stimulation: A Randomized Controlled Cross-Over Trial

Abstract: Background: In a previous functional magnetic resonance imaging study, the authors succeeded in demonstrating the activation of Heschl’s gyrus during auditory hallucinations (AH). Objectives: This study aims to treat AH specifically by repetitive transcranial magnetic stimulation (rTMS). Methods: 16 patients with AH were included in a randomized, cross-over, sham-controlled trial. 1 Hz rTMS was administered over the left and right temporo-parietal cortex and sham position, respectively, on 5 consecutive days; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(37 citation statements)
references
References 64 publications
4
30
1
2
Order By: Relevance
“…These promising results were replicated with an extended duration of stimulation for 2 weeks [17] and with a higher intensity of magnetic field [18][19][20][21] . Conversely, the effect was not replicated by studies with a treatment period only up to 5 days [22,23] or when the magnetic field was administered in the subthreshold intensity [24,25] .…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…These promising results were replicated with an extended duration of stimulation for 2 weeks [17] and with a higher intensity of magnetic field [18][19][20][21] . Conversely, the effect was not replicated by studies with a treatment period only up to 5 days [22,23] or when the magnetic field was administered in the subthreshold intensity [24,25] .…”
Section: Introductionmentioning
confidence: 79%
“…The PET and qEEG were investigated in the resting state within 4 days before and after rTMS treatment. 0.9 Hz of low-frequency rTMS at 100% of MT was administered over the left temporoparietal region defined as the midway between the T 3 and P 3 sites according to the international 10/20 EEG electrode system, as described in previous reports [16,[18][19][20][21] . In our study, we chose the frequency of 0.9 Hz instead of 1 Hz to ensure an inhibitory effect on the brain cortex.…”
Section: Rtms and The Study Protocolmentioning
confidence: 99%
“…For this purpose we used the global AVH, which was evaluated in the majority of studies using the Auditory Hallucination Rating Scale (AHRS) total score [22][23][24][25][26][27][28][29][30][31] or otherwise evaluated by the 20 the Scale for Auditory Hallucinations, 19 or the Psychotic Symptom Rating Scales. 37 The mean gain in each study was computed using the Comprehensive Meta Analysis (version 2) in a random effects model. After computation of the individual effect sizes for each study, meta-analytic methods were applied to obtain a combined, weighted effect size, Hedges's g, for the entire sham group.…”
Section: Quantitative Analysismentioning
confidence: 99%
“…In addition, in some of these studies, the stimulation site was not the left temporoparietal cortex: Some studies targeted the left auditory cortex, [49] some studies stimulated right temporal region [52] and the other studies used bilateral paradigm for stimulation. [51] Although some of the recent studies have reported negative findings, combining them with the studies with positive outcomes resulted in a relatively moderate weighted size effect (about 0.44) indicating promising outcomes which is still statistically significant.…”
Section: Rtms For Hallucinationsmentioning
confidence: 99%